2020
DOI: 10.1038/s41598-020-73756-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-motor symptom burden in patients with Parkinson’s disease with impulse control disorders and compulsive behaviours: results from the COPPADIS cohort

Abstract: The study was aimed at analysing the frequency of impulse control disorders (ICDs) and compulsive behaviours (CBs) in patients with Parkinson’s disease (PD) and in control subjects (CS) as well as the relationship between ICDs/CBs and motor, nonmotor features and dopaminergic treatment in PD patients. Data came from COPPADIS-2015, an observational, descriptive, nationwide (Spain) study. We used the validated Questionnaire for Impulsive-Compulsive Disorders in Parkinson's Disease-Rating Scale (QUIP-RS) for ICD/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
4
11
0
Order By: Relevance
“…First, it is important to note the specific distribution of ICBs in our sample, which is quite similar to that of Jesus et al. (2020) ( Jesus et al., 2020 ).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…First, it is important to note the specific distribution of ICBs in our sample, which is quite similar to that of Jesus et al. (2020) ( Jesus et al., 2020 ).…”
Section: Resultsmentioning
confidence: 73%
“…First, it is important to note the specific distribution of ICBs in our sample, which is quite similar to that of Jesus et al. (2020) ( Jesus et al., 2020 ). In contrast to some studies (see ( Grall-Bronnec et al., 2018 ) for a review), binge eating was the most frequently observed ICB.…”
Section: Resultsmentioning
confidence: 73%
“…A younger age, younger age at PD onset and male sex have been associated with ICDRBs [36,45,46,[58][59][60]. Differences between sexes depending on ICDRBs subtypes were observed, with women developing more compulsive buying and eating disorders and men developing more pathological gambling and hypersexuality disorders [61,62], although the same differences have been reported in the general population [63].…”
Section: Demographic Featuresmentioning
confidence: 85%
“…PD patients with ICDs show a higher level of neuroticism and lower levels of agreeableness and conscientiousness [58], particularly among PD patients with pathological gambling [66] or hypersexuality [10]. Such patients are also reported to have ineffective coping skills [67], premorbid personality (novelty seeking and harm avoidance) [60], and anxiety [68].…”
Section: Personality Traitsmentioning
confidence: 99%
“…In other words, the associations between pain and other nonmotor symptoms may reflect shared protective and risk factors, in addition to possible common pathophysiological mechanisms. Supporting this hypothesis is the reported association between poor quality of sleep and both central parkinsonian pain [ 8 ] and ICDs [ 36 ] in PD. We observed in the present study that patients with central parkinsonian pain had more preserved cognition.…”
Section: Discussionmentioning
confidence: 98%